Diagnostic, Prognostic, and Recurrence Monitoring Value of Plasma CYFRA21-1 and NSE Levels in Patients With Esophageal Squamous Cell Carcinoma - Ju, Mengyang; Ge, Xiaolin; Di, Xiaoke; Zhang, Yumeng; Liang, Liang; Shi, Yujing (Frontiers in Oncology, 2022)
Abstract This study was aimed to evaluate the clinical values of single markers and combination in the diagnosis, short-term efficacy and recurrence risk assessment of esophageal squamous cell carcinoma (ESCC). Methods: Totally 50 patients with I-IVa stage ESCC, 50 healthy controls and 11 patients with recurrent esophageal cancer after comprehensive treatment were enrolled. Serum biomarkers were collected and evaluated. Serum concentrations of carcinoembryonic antigen (CEA), cytokeratin 19 fragment antigen 21-1 (CYFRA21-1) and neuron specific enolase (NSE) were measured by enzyme-linked immunosorbent assay before and after treatment. Results: The diagnostic efficacy ROC curve area of CEA, CYFRA21-1 and NSE in esophageal cancer was 0.70, 0.71 and 0.64(all P <0.05), respectively, the sensitivity was 80%, 88.89% and 60% respectively, and the specificity was 53%, 58.5% and 58% respectively. The sensitivity and specificity of the combined detection were 68% and 78% respectively. The area under ROC curve was 0.75. CEA, CYFRA21-1 and NSE were significantly higher than the healthy control group and thus can be used as diagnostic markers of esophageal cancer (all P <0.05). After standard treatment, the clinical CR and PR rate of patients with positive CYFRA21-1 or NSE before treatment was significantly lower than that of patients with negative CYFRA21-1 or NSE (X2=4.52 ,P =0.03). A significant negative correlation was found between N stage and clinical efficacy (HR 2.48, 95%CI 1.07-5.73). After comprehensive treatment, the serum CYFRA21-1 and NSE levels in recurrent patients also increased significantly(all P<0.05), indicating these two markers play obvious roles in recurrence monitoring. Conclusion: CYFRA21-1 and NSE may help to predict the response of ESCC to CRT, and play important roles in the diagnosis and recurrence monitoring of esophageal cancer. These markers have a diagnostic value of esophageal cancer when combined with CEA.